How to measure service quality in public transport sector - Nemecz, Gábor (Studia Mundi – Economica, 2019)
Measuring the quality (satisfaction) is at least as important in transport sector as in other economic sectors since sustainability of society as a whole is at stake. The objective is not only to increase the satisfaction of the existing passengers but to attract potential new users into the system. I have analysed the methodology and the process of different surveys completed in three European cities which can serve as a starting point for surveying public transport in the capital.